Keeping One's Distance: Mask Wearing is Implicitly Associated With Psychological Distance. Issue 4 (May 2022) - Fatfouta, Ramzi; Trope, Yaacov
Mask wearing plays a vital role in the fight against the novel coronavirus (COVID-19). Despite its ubiquity in everyday social life, it is still unknown how masked faces are mentally represented. Drawing on construal-level theory, we test the hypothesis that masked faces and unmasked faces are implicitly associated with psychological distance and proximity in memory, respectively. Four preregistered, high-powered experiments ( N = 354 adults) using the Implicit Association Test lend convergent support to this hypothesis across all four dimensions of psychological distance: social distance, spatial distance, temporal distance, and hypothetical distance. A mini meta-analysis validates the reliability of the findings (Hedge's g = 0.46). The present work contributes to the growing literature on construal-level effects on implicit social cognition and enriches the current discussion on mask wearing in the pandemic and beyond.